A Study of Implementation Fresnel Lens with Tracking Positioning Ability to Achieve Optimum Concentrated Heat on the Solar Heater Element - Nawawi, Muhammad Amirul Haziq; Baharom, Md Nor Ramdon (Progress in Engineering Application and Technology, 2024)
This study investigates the use of Fresnel lenses with tracking capabilities to enhance the heating efficiency of solar heater elements. The primary objective is to optimize solar energy utilization by maintaining optimal alignment of the lens with the sun. The project involves developing a system that integrates light sensors, servo motors, and an Arduino microcontroller to control the lens’s position. Experiments were conducted to measure the temperature increase in a fluid contained within a metal pipe when exposed to concentrated sunlight. The results demonstrated significant improvements in heat concentration, highlighting the effectiveness of this approach. This research underscores the potential of this technology to advance solar power generation and reduce dependence on conventional energy sources.